An African-Communitarian Response to Robert Nozick's Political Philosophy - Obioha, Uwaezuoke Precious; Adegboyega, Oyekunle Oluwayemisi (NIU Journal of Humanities; Vol 5 No 1 (2020): KIU Journal of Humanities, Vol. 5 No. 1, March 2020, 2020)
Robert Nozick’s attempt to contribute to the existing corpus on the best possible way to achieve a good human community conducive for the realization and flowering of human well-being must be seen as a bold step to change the political cum socio-economic landscape of the world environment. This is expected of every political philosopher, to deploy his/her wealth of philosophical arsenal towards changing our world and making it conducive for the achievement of the summum bonnum . However, Nozick’s political thoughts have far reaching implications for human well-being and the establishment of a good human community. The paper through the analytical and critical methods of a philosophical research, argues against certain positions which Nozick has taken in his political thoughts. The paper claims that Nozick’s thought sparks an extreme form of unbridled individualism and that Nozick's entitlement theory lacks the human feelings of sympathy, co-existence, acceptance, care and concern requisite for building a good human community. The paper finally advocates for a political thought and arrangement that tries to minimize the plights and the sufferings of the disadvantaged and worse off members of the human community made possible through the virtues of sympathy, love, compassion, acceptance, co-existence and care espoused in African Communitarian idea of justice.